THE OPTIMIZING STRATEGY OF LEARNING LABORATORY SKILL TO INCREASE THE COMPETENCE OF CONFINEMENTS IN HEALTH EDUCATION - Toyibah, Afnani; Hamarno, Rudi (University of Muhammadiyah Malang, 2011)
This research is accomplished to find the best drawing of skill laboratory learning in coping of confinements as the effort of learning optimality so that it is able to increase the competence of nursery help in work field. Research design uses descriptive qualitative method based on empiric and normative approach. Sampling technique uses interviewing, documentation and observing. The interviewing is done to 9 informants so that it can get the document which deals with the research problems. Observation is done toward the process of laboratory learning skill in coping confinement and laboratory condition in Malang nursery program. Data analysis uses descriptive based on MilesHuberman and SWOT analysis. Research results are the reason why we need to optimize laboratory learning skill in coping a confinement since it is not applied optimally for students, learning substance which need to be optimized are unsystematic planning which has not showed a specific purpose,implementation system, evaluation and schedule, the sequence of learning laboratory skill, evaluation system which bases on student?s work, worst supporting system. The optimizing strategy of learning laboratory skill are it should have a systematic plan such as having an purpose explanation, schedule arrangement, method arrangement and procedures base on the accepted schedule, the laboratory skill application should be sequence based on the practice guidance, the evaluation should base on student?s work , raw input needs to be measured since supporting system really influence the learning process.